Iterative Krylov methods for large linear systems - Vorst, H. A. van der, 1944- (Cambridge monographs on applied and computational mathematics ;, 2003)
Based on extensive teaching by the author, this book presents an overview of a number of Krylov projection methods for the solution of linear systems of equations. There are a large number of references for further reading as well as exercises to help students as they first encounter the material.